Dynamical interactions between Loop Current and Loop Current Frontal Eddies in a HYCOM ensemble of the circulation in the Gulf of Mexico - Yang, Xingchen; Le Hénaff, Matthieu; Mapes, Brian; Iskandarani, Mohamed (Frontiers in Marine Science, 2023)
The dynamics of the Loop Current (LC) system in the Gulf of Mexico (GoM), specifically during the shedding of Eddy Franklin in 2010, is investigated using an ensemble of simulations. The ensemble members differed in their initial conditions of the West Florida Cyclonic Eddy (WFCE), which in turn significantly influences the timing and occurrence of the Loop Current Eddy (LCE) detachment. The results reveal that a stronger and larger WFCE leads to an early LCE detachment, while a weaker and smaller WFCE results in late or even no detachment within the 60-day simulation period. The initial WFCE’s size and strength are also found to impact the evolution of Campeche Bank Cyclonic Eddies (CBCE). The intrusion of a large and strong WFCE into the LC leads to a rapid growth of potential vorticity (PV) over the eastern Campeche Bank (CB), associated with the formation of a CBCE. In addition, ensemble members with stronger and larger WFCE generally agree with mooring data regarding the velocity evolution over the eastern CB, as well as the CBCE’s northeastward offshore displacement. Our results suggest that the size and strength of the WFCE may serve as predictors of the formation of a CBCE and of an LCE detachment occurrence. This finding has implications for future studies and forecasting methodologies for the GoM circulation.